Caracterização da população, criação e sanidade de bicudo (Sporophila maximiliani) em cativeiro no Estado de Minas Gerais - Thiago Lima Stehling (2019)
The Great-billed seed-finch Sporophila maximiliani (Cabanis, 1851), is a bird of the Passeriform Order and Family Thraupidae, native in Brazil. In the country, the species is considered Critically Endangered, which indicates an extremely high risk of extinction. They are rare in nature but abundant in legalized breeders. This study aims to hold a diagnosis of the captive population, evaluate the forms of Great-billed seed-finch receiving and its destination in the CETAS of Minas Gerais, to carry out a questionnaire directed to the species´ commercial breeders, as well as determining the occurrence of Chlamydia psittaci and endoparasitosis infection in Great-billed seed-finches that are in captivity in the state of Minas Gerais. In the year of 2017, there were 175,718 Great-billed seed–finch registered in Brazil, allocated among 29,333 amateur breeders. In Minas Gerais, 24 commercial establishments were registered, and a total of 3,665 ones in 2017, in the same state, in the year of 2019 30,285 animals were registered in amateur farms. In the city of Belo Horizonte, in 2019, the number was of 4,699 birds, and 767 amateur breeders. The main ways of receiving the Great-billed seed-finch in the CETAS of Minas Gerais, between the years of 2013 and 2017, were the seizures done by the environmental inspection agencies and the voluntary delivery held by citizens. The allocations of the Great-billed seed –finch received by the CETAS in Minas Gerais from 2013 to 2017 were divided into releases (42%), death (33%), commercial (14%) and maintenance (11%). Eleven Great-billed seed –finch breeders from the State of Minas Gerais were interviewed. Properly registered in the environmental agencies, and through the questionnaire, they have answered questions related to breeding, management, nutrition, diseases, reproduction, market, singing tournaments and conservation programs. Of the two hundred and four fecal samples analyzed (n = 204), provided from 11 breeders, one hundred and fifty of them, equivalent to 74% of the samples, were positive for the presence of oocysts in the faeces. Of the 66 individuals tested for the presence of Chlamydia psittaci, 100% of them were negative to PCR.